Design of a Technician Attendance System for Internet Network Disturbances at PT Telkom Indonesia Using a Website - Ardiansyah, Fery; Irwan; Lubis, Akhyar (Bahasa Indonesia, 2024)
Telkom Indonesia, or PT Telkom Indonesia (Persero) Tbk, is a telecommunications company based in Indonesia. Telkom Indonesia was founded in 1856 under the name "Jawatan Telegraaf" by the Dutch East Indies Government. In 1965, the company name changed to "Perum Telkom" after being taken over by the Indonesian government. Telkom Indonesia is a State-Owned Enterprise (BUMN) which is wholly owned by the Indonesian government. PT Telkom Indonesia is a company that continues to develop communications media and internet network technology. At PT Telkom Indonesia which has a branch office in Medan City, precisely on Jalan Gunung Krakatau No. 17 A North Sumatra Province. The branch office has employees who work in the technician field, where many technicians are on duty in the field to fix network problems. The problem that occurs in this company is that many technicians do not fill in the attendance data that has been provided with the finger print machine at the Medan City branch of PT Telkom. This happens because many technicians who are on duty in the field to repair customers' internet networks in Medan City are reluctant to return to the office or go directly to the location to repair the internet network, so the technician employees forget to fill in the attendance data provided by the company. For this reason, the company requires an online presence that is intended for network trouble technicians.